The language of Chariton of Aphrodisias: morphological characteristics - Sanz Morales, Manuel (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
The present contribution is the fi rst to study the morphological characteristics of Chariton of Aphrodisias’s language as a whole. After a thorough analysis of each relevant feature, it can be concluded that Chariton does not use an atticist language, because the features of the Hellenistic koine are predominant: while some of them co-exist with the corresponding attic traits, others are exclusive for the koine. However, some exclusive attic features can be found as well, although not on a systematic basis. This allows us to draw a second conclusion: Chariton’s prose shows classicist characteristics, but it cannot be considered atticist prose yet.